The Distance between the Pectoralis Major Tendon Insertion and the Top of the Humeral Head is a Reliable Landmark: An Anatomic Study - Sahu, Dipit; Jagiasi, Jairam D.; Valavi, Anisha S.; Ubale, Tushar (Joints, 2019)
Purpose This study aimed to analyze the distance between the superior edge of the pectoralis major and the top of the humeral head and evaluate whether this distance is a consistent measurement.Methods Twenty-two shoulders in eleven cadavers were dissected and the attachment of the pectoralis major tendon was preserved. Two distances were recorded with the help of digital vernier caliper: the distance between the upper edge of pectoralis major and tangent to the top of humeral head (PM–T) and the distance between the superomedial tip of greater tuberosity (GT) and the upper edge of the pectoralis major tendon (PM–G; ± standard error of the means).Results The mean PM–T distance was 53.8 mm (±0.8 mm) and the mean PM–G distance was 46.8 mm (±0.9 mm). The distance between the top of humeral head and tip of the GT was 7 mm. The PM–T distance was a significant outlier in three shoulders as it inserted high on the humerus.Conclusion We can conclude that the PM–T and PM–G distances were a consistent measurement.Clinical Relevance The distance between the pectoralis major tendon and top of the humeral head was measured in this study as a reliable method that can be used intraoperatively to decide the height of the humerus prosthesis in comminuted fractures of the proximal humerus.
Keywords: cadaver study; shoulder hemiarthroplasty; pectoralis major; tendon insertion; humeral head